A novel bilayered expanded polytetrafluoroethylene glaucoma implant creates a permeable thin capsule independent of aqueous humor exposure. Issue 1 (22nd August 2020) - Bicket, Amanda Kiely; Szeto, Julia; Roeber, Peter; Towler, Jeff; Troutman, Mitch; Craven, E. Randy; Khatana, Anup; Ahmed, Ike; Quigley, Harry; Ramulu, Pradeep; Pitha, Ian F.
Abstract: The purpose of these studies was to evaluate clinical, functional, and histopathological features of glaucoma drainage implants (GDIs) fabricated from novel, custom‐tailored expanded polytetrafluoroethylene (ePTFE). Implants of matching footprints were fabricated from silicone (Control) and novel, bilayered ePTFE. ePTFE implants included: (a) one that inflated with aqueous humor (AH) (High), (b) one that inflated with a lower profile (Low), (c) an uninflated implant not connected to the anterior chamber (Flat), and (d) one filled with material that did not allow AH flow (Filled). All implants were placed in adult New Zealand White rabbits and followed over 1–3 months with clinical exams and intraocular pressure. The permeability of tissue capsules surrounding GDIs was assessed using constant‐flow perfusion with fluoresceinated saline at physiologic flow rates. After sacrifice, quantitative histopathological measures of capsule thickness were compared among devices, along with qualitative assessment of cellular infiltration and inflammation. Capsular thickness was significantly reduced in blebs over ePTFE (61.4 ± 53 μm) versus silicone implants (193.6 ± 53 μm, p = .0086). AH exposure did not significantly alter capsular thickness, as there was no significant difference between High and Filled (50.9 ± 29, p = .34) implants. Capsules around ePTFE implants demonstrated permeability with steady‐state pressure: flow relationships at physiologic flow rates and rapid pressure decay with flow cessation, while pressure in control blebs increased even at low flow rates and showed little decay. Perfused fluorescein dye appeared beyond the plate border only in ePTFE implants. ePTFE implants are associated with thinner, more permeable capsules compared to silicone implants simulating presently used devices.